14-3-3 Proteins and photoneuroendocrine transduction: role in controlling the daily rhythm in melatonin. (August 2002) - Klein, D. C.; Ganguly, S.; Coon, S.; Weller, J. L.; Obsil, T.; Hickman, A.; Dyda, F.
Abstract : This paper describes the role 14-3-3 proteins play in vertebrate photoneuroendocrine transduction. 14-3-3 proteins form a complex with arylalkylamine N-acetyltransferase (AANAT), the enzyme which turns melatonin production on during the day and off at night. Complex formation is triggered at night by cAMP-dependent phosphorylation of the enzyme, and results in activation and protection against proteolysis. This enhances melatonin production > 10-fold. Light exposure results in dephosphorylation of the enzyme and disassociation from 14-3-3, leading to destruction and a rapid drop in melatonin production and release and circulating levels.